PEMANFAATAN TEPUNG KACANG MERAH DAN SALAK PADANG SIDIMPUAN (Salacca sumatrana R.) DALAM PEMBUATAN SNACK BAR - Siregar, Linda Nopita Sari; Harun, Noviar; Rahmayuni, Rahmayuni (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The study was purpose to get the best combination of red bean flour and  Padang sidimpuan (Salacca sumatrana R.)bark.The research used a Complete Randomized Design (CRD) with 5 treatments and 3 replications.The treatments were red bean flour 70%: bark fruit30%, red bean flour60%: bark fruit40%, red bean flour 50% : bark fruit 50%, red bean flour40%: bark fruit60%and red bean flour30%: bark fruit 70%.  The data obtained were analyzed statistically using Anova and DNMRT at 5%.Theresearch showed that using redbean flour and bark fruit were significant on water content, ash content, fat content, crude fiber content, protein content, carbohydrate content and sensory test. The best treatment of snack bar from this research was red bean flour 40% : bark fruit 30%which had water content 23,31%, ash content 1,84%,fat content 14,44%, crude fiber content 8,57%, protein content 13,45%, carbohydrate content 46,94%. light brown on colour outsideand yellowish brown on colour inside, red bean flour and fruit flavour, red bean flour and fruit taste, the texture creamy and dense and overall assesment of snack bar was  preferred by the panelists.  Keywords :Snack bar, red bean flour and bark fruit.